2017
DOI: 10.1016/j.landurbplan.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Attractive, climate-adapted and sustainable? Public perception of non-native planting in the designed urban landscape

Abstract: h i g h l i g h t s• 75.3% participants positive about climate-adapted non-native planting.• Climate change identified as major driver of acceptance of non-native plants.• Acceptance also related to aesthetics, context, perceived invasiveness.• Perceived attractiveness not related to perceived nativeness.• Contradictions in perception of non-native plants identified. a b s t r a c t Throughout Europe climate change has rendered many plant species used in contemporary urban planting design less fit for use in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 43 publications
2
35
1
1
Order By: Relevance
“…A special issue was the use of large-sized plants for landscaping the front of the building, while there was a need to consider yet another important factor -the reaction of public opinion to both the biodiversity of urban planting and the landscaping process as a whole [15,16]. As a result, a variant was proposed that visually brought out the beauty of the facade in a row planting of Pópulus álba.…”
Section: Fig1 Vegetable Composition In the Form Of A National Ornamentmentioning
confidence: 99%
“…A special issue was the use of large-sized plants for landscaping the front of the building, while there was a need to consider yet another important factor -the reaction of public opinion to both the biodiversity of urban planting and the landscaping process as a whole [15,16]. As a result, a variant was proposed that visually brought out the beauty of the facade in a row planting of Pópulus álba.…”
Section: Fig1 Vegetable Composition In the Form Of A National Ornamentmentioning
confidence: 99%
“…aesthetic (e.g. Hull, 1992;Parsons, 1995;Fuller et al, 2007;Hoyle, Hitchmough and Jorgensen, 2017;Southon et al, 2017) and this has been reflected in the management of urban hedges (Oreszczyn, 2000;Oreszczyn and Lane, 2000;Faiers and Bailey, 2005;Gosling et al, 2016).…”
Section: Benefits Of Nature Within Our Citiesmentioning
confidence: 99%
“…Even when people appreciate the benefit of improving ecological quality they may not wish to do so at the expense of the attractiveness of their neighbourhoods (Nassauer, 1995). Todorova et al (2004) and Hoyle et al (2017) found that people enjoyed seeing flowers incorporated in to their street plantings and that they offered benefits to psychological wellbeing (Todorova, Asakawa and Aikoh, 2004). Colourful non-natives in ordered formation were found to be the most aesthetically pleasing and to a lesser extent were generally thought to offer the greatest benefit to invertebrates (Todorova, Asakawa and Aikoh, 2004), however this is unlikely to be the case.…”
Section: Public Perception Of Urban Greeningmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is the concept of native/exotic species. Hoyle and colleagues [14] investigated the public perception of non-native plants in gardens highlighting key factors that are actively driving acceptance or rejection of a given landscape by the public. As expected, the aesthetically pleasing appearance was one of them: beautiful flowers are accepted and planted in gardens, independently from their country of origin.…”
mentioning
confidence: 99%